CONCEPT AND PROBLEMS OF APPROPRIATE EDUCATION IN THE FAMILY LAW OF UKRAINE - Тімуш, Ірина Сергіївна; Тімуш, Діана Ігорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: in the article the scientific-theoretical analysis of the content of the concept «foster parenting», «foster family» in legal science is carried out. The legal status and values of the foster family in the field of providing family care for orphans and children deprived of parental care are determined. Methods: analysis of the essence of the concept of «Foster Care», «adoption», «guardianship» in areas such as placements of children, grounds care for orphans / persons who are deprived of parental care, purpose, result. Results: theoretical-methodical aspects of the concept «foster parenting» are researched. The analysis of information characterizing foster families, orphans, persons deprived of parental care is carried out. The conclusion is made on the need to regulate the issue of foster care in the family law of Ukraine. Discussion: problems of placement of orphans / persons deprived of parental care, the problem of the interpretation of the concept of «foster parenting», «adoption» in the legal sense. The family gives human life, education, primitive socialization and all that without which a person can not live and exist and acts as a definite defender and guardian of the private form of a human way of life. Only in the family is a complete transfer of parental experience. The family adopts cultural customs and foundations, ensures the continuity of traditions, forms the value base of the individual. In short, the family is the basis of social life. Every orphan or child who was deprived of parental care under certain circumstances of life deserves to be full of love and protection of mother and father. By its very nature, the system of foster care is intended to ensure the proper upbringing and maintenance of orphans and children deprived of parental care.